The Impact of AI on Leadership: New Strategies for A Human - Machine - Cooperation (Global Journal of Management and Business Research, 2022)
AI is about to revolutionize the business world As much as AI algorithms are widely used in many companies today development is still in its infancy But what is evident is that AI is a challenge to leadership and will also profoundly change the way companies are managed This chapter discusses recent proposals for an alliance between those in charge and AI As it turns out there are two approaches to this synergy